2019
DOI: 10.1002/cam4.2220
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐4286 promotes cell proliferation, migration, and invasion via PTEN regulation of the PI3K/Akt pathway in non‐small cell lung cancer

Abstract: It is well‐known that phosphatase and tensin homologue deleted on chromosome 10 (PTEN) is a tumor suppressor which negatively regulates PI3K/AKT signaling and is activated widely in non‐small cell lung cancers (NSCLC). However, genetic alterations in PTEN genes are rare, suggesting an undefined mechanism(s) for their suppression. Notably, growing evidence indicates that PTEN can be regulated by microRNAs involved in cancer progression. In this study, we discover that the miR‐4286 is overexpressed in NSCLC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 30 publications
(60 reference statements)
3
33
0
Order By: Relevance
“…MiR-4286 is another miRNA that was found to be upregulated in the radioresistant group in our study. In previous studies, its upregulation is also found to be associated with cell proliferation, migration, and invasion via targeting of PTEN and Runx3 (26,27). As for the downregulated miRNAs identified in our work, miR-1275 was reported to inhibit cell migration and invasion in gastric cancer, while the downregulation of miR-1275 by H3K27me3 could mediate glial induction of GBM cells (28,29).…”
Section: Discussionsupporting
confidence: 70%
“…MiR-4286 is another miRNA that was found to be upregulated in the radioresistant group in our study. In previous studies, its upregulation is also found to be associated with cell proliferation, migration, and invasion via targeting of PTEN and Runx3 (26,27). As for the downregulated miRNAs identified in our work, miR-1275 was reported to inhibit cell migration and invasion in gastric cancer, while the downregulation of miR-1275 by H3K27me3 could mediate glial induction of GBM cells (28,29).…”
Section: Discussionsupporting
confidence: 70%
“…In addition to the clinical value of miRNAs, their functional roles in tumor progression have also been investigated, providing further evidence for the therapeutic potential of these miRNAs (32). In the pathogenesis of NSCLC, several miRNAs, such as miR-612 (33), miR-421 (3) and miR-4286 (34), were reported to be involved in tumor cell proliferation, migration and invasion and thus may serve as potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…As a tumor suppressor, PTEN has been associated with several biological processes, including maintenance of genomic stability, cell survival, migration, proliferation and metabolism (38). Recently, a number of studies revealed that PTEN downregulation was associated with poor prognosis in several types of cancers, including breast, prostate and non-small cell lung cancers (39)(40)(41). Moreover, loss of PTEN expression has been implicated in the promotion of OS cell proliferation and metastasis (42).…”
Section: Discussionmentioning
confidence: 99%